Curriculum Innovation: a Comparasion ‎Between the Goals and the Facts on 2013 ‎Curriculum Implementation at Madrasah ‎Aliyah in Kabupaten Tolitoli - Hamka; Muhammad Nur Asmawi (State Islamic Institute of Madura, 2022)
Curriculum 2013 (K13) is one form of innovation in the field of education initiated by the Indonesian government. It is necessary to explore adopters' perceptions of this innovative product as a top-down innovation model. The adoption of an innovative product is strongly influenced by, among others, the adopter's perspective on the product's relative advantage, compatibility, and complexity. This study examines the influence of these three factors on the decisions of teachers (adopters) in adopting or implementing K13 in their learning practices. This problem is studied using a mixed-method, quantitative method as the primary approach and supported by a qualitative approach. The regression analysis test results show a combined effect of the relative advantage, compatibility, and complexity factors on implementing K13 with a correlation of 18.2%. Still, partially there is no influence between the factors of advantage and complexity on the implementation of K13. This shows that the adoption of K13 innovation is more widely accepted as a necessity, not because of a positive perception of K13 itself. Their lack of knowledge of K13 influences the adopter's perception of K13 at the concept and implementation techniques level. The results of this study recommend the need for intensive training for teachers in optimizing the implementation of K13 as expected.